Optimization, Production, Purification of Laccase Enzyme from Bacillus sp - Tamilvanan, Nivedharshini (Journal of New Developments in Chemistry, 2020)
Laccase enzyme production is important and more beneficial for environment, because it has many roles like, involved in bioremediation, biodegradation, decolorization of environmental polluted dyes and pharmaceutical sector also. Production of laacse enzyme from bacillus sp as using of Agro waste (rice bran) as a substrate. The Agricultural soil sample was collected, after the sample were processed for the preliminary and biochemical tests to identification of Bacillus organism. The Guiacol inducer were used for microbial screening of laccase enzyme production. After that microbial screening, various optimization parameters (pH, Temperature, Inducers, carbon and nitrogen sources) are checked for that production of laccase enzyme in mass level. Based on that optimization the bulk fermentation (large scale) (solid state fermentation) were done as a rice bran substrate. The fermentation product was subjected to analyzed the physiochemical properties and purification based on that techniques of Gel filtration chromatography, Dialysis, Ammonium sulfate preciptation. The protein estimation of that product to analysed by lowry’s method.
Keywords: Laccase; Solid State Fermentation; Dialysis; Protein estimation; Bacillus sp; Gel filtration chromatography